2022
DOI: 10.1016/j.jhep.2021.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to environmental contaminants is associated with altered hepatic lipid metabolism in non-alcoholic fatty liver disease

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(117 citation statements)
references
References 49 publications
6
111
0
Order By: Relevance
“…Recently, increased levels of primary bile acids have been linked to risk of HCC in humans [60]. Animal and human studies also suggests that PFAS impact bile acid metabolism, increasing risk of liver injury [34,61]. The third compound associated with both PFOS and HCC was Butyric acid, a short chain fatty acid which is primarily produced via intestinal fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, increased levels of primary bile acids have been linked to risk of HCC in humans [60]. Animal and human studies also suggests that PFAS impact bile acid metabolism, increasing risk of liver injury [34,61]. The third compound associated with both PFOS and HCC was Butyric acid, a short chain fatty acid which is primarily produced via intestinal fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, PFAS have also been linked to alterations in cytokeratin 18, a marker for liver apoptosis [32,33]. Recent evidence also suggests that PFAS are associated with increased risk of NAFLD, diagnosed using liver MRI or liver biopsy, in both children and adults [34,35]. Using untargeted metabolomics, these studies have also shown that alterations in lipid and amino acid metabolism link PFAS exposure and risk of NAFLD [34,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 ). Therefore, we have utilized ChemRICH analysis ( Barupal and Fiehn, 2017 ) to identify the PFOA associated chemical sets, which suggested that PFOA exposure has a negative effect on most of the lipid sets except triglycerides ( Sen et al, 2022 ; Sinisalu et al, 2020 ). PFOA exposure may have also induced the amino acid and tocopherol metabolism pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Identifying these chemical sets can assist in understanding the systematic metabolic effect of PFOA exposure which can span over multiple metabolic pathways (Figure 8). Therefore, we have utilized ChemRICH analysis 77 to identify the PFOA associated chemical sets, which suggested that PFOA exposure has a negative effect on most of the lipid sets except triglycerides 79, 80 . PFOA exposure may have also induced the amino acid and tocopherol metabolism pathways.…”
Section: Resultsmentioning
confidence: 99%